Frequency of MED12 mutations in phyllodes tumors: Inverse correlation with histologic grade. Issue 6 (3rd March 2016) - Yoon, Nara; Bae, Go Eun; Kang, So Young; Choi, Mi Sun; Hwang, Hye Won; Kim, Seok Won; Lee, Jeong Eon; Nam, Seok Jin; Gong, Gyungyub; Lee, Hee Jin; Bae, Young Kyung; Lee, Ahwon; et al.
Abstract : Phyllodes tumor (PT) is a rare breast biphasic tumor with a potential risk of recurrence and metastasis. In this study, the frequency of MED12 mutations in 176 PTs (49 benign, 49 borderline, and 78 malignant) was determined and the prognostic effect of these mutations in malignant type PT was evaluated. Analysis of MED12 mutations was performed by Sanger sequencing targeting the hotspot mutation region (exon 2) of MED12 . Immunohistochemistry was also applied for evaluation of MED12 protein expression on tissue microarray blocks for 133 PTs including 50 benign, 50 borderline, and 33 malignant cases. A notable difference in the frequency of MED12 mutations was found according to histologic grade (71.4% of benign PTs, 51% of borderline PTs, 26.9% of malignant PTs; P  < 0.001). MED12 protein expression was not correlated with MED12 mutation status. Patients with malignant PTs that harbored MED12 mutations demonstrated improved disease‐free survival (DFS) compared with those without MED12 mutation ( P  = 0.07). MED12 mutation was a common molecular alteration in PT and the frequency of MED12 mutation decreased with increasing histologic grade. In malignant PT, MED12 exon 2 mutations showed improved DFS but without significance. © 2016 Wiley Periodicals, Inc.